Strong earthquake recurrence interval in the southern segment of the Red River Fault, southwestern China - Zhou, Qingyun; Li, Xi; Chang, Yuqiao; Yu, Jiang; Luo, Weidong; Bai, Xianfu (Frontiers in Earth Science, 2023)
Along the southeastern margin of the Tibetan Plateau, an important boundary fault, known as the Red River Fault (RRF), formed during the extrusion of mantle and lower crustal materials beneath the Tibetan Plateau. The characteristics of RRF activity are important for understanding the tectonic evolution of the southeastern margin of the Tibetan Plateau. There is less knowledge about the strong earthquake recurrence interval in the southern segment of the RRF than about its northern segment. In this study, based on the characteristics of the active tectonic landform, three paleoseismic trenches were excavated in Adipo Village north of Honghe County in the southern segment of the RRF. In these trenches, three paleoseismic events that occurred in the middle and late Holocene were identified. According to the 14 C dating results, these events were constrained to 785-504 BC, 26-492 AD, and 1415-1857 AD. The average earthquake recurrence interval was determined to be approximately 960-1320 a.